Los Angeles today and tomorrow : results of the Los Angeles 2000 community survey - Berry, Sandra H., 1949-; Los Angeles 2000 Committee; Rand Corporation; John Randolph Haynes and Dora Haynes Foundation (Santa Monica, CA : RAND, 1988)
This report describes a survey undertaken to determine how the people of Los Angeles feel about the quality of their lives, what they see as the region's most serious problems, how they rate the way the problems are being handled, and what they think can and should be done. The survey results, which will help the Los Angeles 2000 Committee develop a strategic plan for the region's future, indicate that (1) most of the area's residents think that life in Los Angeles is good, but are concerned that the future may be less good; (2) people generally agree that quality of life depends most on controlling crime, protecting the environment, and providing good schools; and (3) most people support measures to make life better, including regulating growth and raising some kinds of taxes. Despite general agreement, there are important differences in the levels of concern expressed by different groups about area problems and about what they value most in their communities. These differences strongly follow racial, ethnic, and economic class lines.
"October 1988."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Public opinion -- California -- Los Angeles Region; Quality of life -- California -- Los Angeles Region -- Public opinion; Regional planning -- California -- Los Angeles Region -- Public opinion; Los Angeles Region (Calif.) -- Population -- Public opinion; Los Angeles Region (Calif.) -- Social conditions -- Public opinion